Methyl 3,4-Dihydroxybenzoate Induces Neural Stem Cells to Differentiate Into Cholinergic Neurons in vitro - Pan, Jun-Ping; Hu, Yang; Wang, Jia-Hui; Xin, Yi-Rong; Jiang, Jun-Xing; Chen, Ke-Qi; Yang, Cheng-You; Gao, Qin; Xiao, Fei; Yan, Li; Luo, Huan-Min (Frontiers in Cellular Neuroscience, 2018)
Neural stem cells (NSCs) have been shown as a potential source for replacing degenerated neurons in neurodegenerative diseases. However, the therapeutic potential of these cells is limited by the lack of effective methodologies for controlling their differentiation. Inducing endogenous pools of NSCs by small molecule can be considered as a potential approach of generating the desired cell types in large numbers. Here, we reported the characterization of a small molecule (Methyl 3,4-dihydroxybenzoate; MDHB) that selectively induces hippocampal NSCs to differentiate into cholinergic motor neurons which expressed synapsin 1 (SYN1) and postsynaptic density protein 95 (PSD-95). Studies on the mechanisms revealed that MDHB induced the hippocampal NSCs differentiation into cholinergic motor neurons by inhibiting AKT phosphorylation and activating autophosphorylation of GSK3β at tyrosine 216. Furthermore, we found that MDHB enhanced β-catenin degradation and abolished its entering into the nucleus. Collectively, this report provides the strong evidence that MDHB promotes NSCs differentiation into cholinergic motor neurons by enhancing gene Isl1 expression and inhibiting cell cycle progression. It may provide a basis for pharmacological effects of MDHB directed on NSCs.